1996
DOI: 10.5636/jgg.48.675
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Dynamics of the Magnetospheric Tail Induced by Substorms: A Multisatellite Study

Abstract: The large scale dynamics ofthe tail during substorms are examinedusing multi-satellite measurements made between 18 and 22:00 UT on August 22, 1983. We use data from ISEEI/2, 1977-007, IMP-8, and ISEE-3 located in the solar wind or tail at distances along the Sun-Earth line ranging from +11 to -205RE. During the period studied, which corresponded to a southward directed IMF, successive plasma injections were detected at 6.6RE first during a general increase of the magnetic field in the lobe. The magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…These boundary motions can hardly be related to a plasmoid as a widening of the tail is expected from such a high‐pressure structure. Previous work has indeed shown, as expected, that plasmoids lead a satellite located in the distant magnetosheath to pass inside the lobe [e.g., Sauvaud et al , 1996], i.e., the reverse motion of what is observed for the cases presented here.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…These boundary motions can hardly be related to a plasmoid as a widening of the tail is expected from such a high‐pressure structure. Previous work has indeed shown, as expected, that plasmoids lead a satellite located in the distant magnetosheath to pass inside the lobe [e.g., Sauvaud et al , 1996], i.e., the reverse motion of what is observed for the cases presented here.…”
Section: Resultssupporting
confidence: 84%
“…Magnetopause motions in the far tail have already been shown to be induced by substorm associated processes: a study performed from simultaneous IMP‐8 and ISEE‐3 data by Sauvaud et al [1996] has shown a characteristic time delay of 40 min between cross‐tail current disruption onset occurring in the near‐Earth plasma sheet and the enhancement of the tail diameter at 205 R E . The observed signatures were in agreement with the concept of the ejection of plasmoids from the magnetospheric tail and the tailward propagation of a compression region with enhanced pressure, so that the ISEE‐3 satellite initially in the distant magnetosheath was entering the magnetosphere when the high‐pressure region reached its location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing the large-scale dynamics of the magnetospheric system during substorms has motivated a number of studies in the recent years, and it is still one of the main areas of magnetospheric research. Magnetic field observations in the equatorial region of the inner magnetosphere and farther in the magnetotail lobe have shown that a reconfiguration of the magnetic field topology ("dipolarization") linked to a partial disruption of the near-Earth cross-tail current is associated with substorm onsets detected as breakups of auroral forms in the ionosphere [e.g., Sauvaud and Winckler, 1980;Lui, 1988, as the plasma sheet recovery (thickening) and the release of plasmoids from the far tail [e.g., Hones et al, 1967Hones et al, , 1984Scholer et al, 1984;Sauvaud et al, 1996;Nagai et al, 1997Nagai et al, , 1998].…”
Section: Introductionmentioning
confidence: 99%
“…By fitting the data with a simple disrupted current slab whose tailward boundary propagates tailward, as well as using multipoint measurements (ISEE, IMP‐8 and INTERBALL‐Tail), it was concluded that the CD started at 6–9 R E and propagated down the tail with a velocity of the order of 150–350 km/s over tens of R E during substorm expansion phases [ Jacquey et al , 1991, 1993, 1998; Ohtani et al , 1992; Jacquey and Sauvaud , 1994]. Furthermore, direct comparisons of IMP‐8 and ISEE‐3 data during a major substorm led to linking CD and plasmoids ejected from the tail at ≈20 R E , and observed in the far tail during a major disruption [ Sauvaud et al , 1996a, 1996b].…”
Section: Observationsmentioning
confidence: 99%